The Adaptation Process of Families With Children With Intellectual Disabilities in Catalonia. Issue 4 (October 2016) - Mas, Joana Maria; Giné, Climent; McWilliam, Robin A.
Abstract : The most important adaptation task that all families must undertake is the construction of a sustainable, meaningful, and congruent daily routine of family life (R. Gallimore, T. Weisner, L. Bernheimer, D. Guthrie, & K. Nihira, 1993 ). The aim of this mixed-method study was to understand, from the perspective of parents, how families adapt their family routines to rearing a 3- to 5-year-old child with intellectual or developmental disabilities to guarantee a sustainable family routine. Accordingly, this study focused on accommodations—changes that parents make or do not make because of the child's disabilities; ecological and cultural elements explaining why parents make or do not make a specific accommodation; and the sustainability of the family routine. Eighteen families with a preschooler who attended an early intervention center in Catalonia, Spain, participated in interviews and completed a series of questionnaires. The main instrument used was the Ecocultural Family Interview adapted for the Catalonian context. Results show the importance of different cultural and ecological elements in the family's accommodation processes, such as parents' jobs, services for the child, perceived support, information, and—especially—the need for professionals (and researchers) to understand family adaptation in terms of the importance of building a sustainable family routine.